Evaluating the performance of GCC banks using camel framework - Al-Musai, Mohammed Ali Ahmed (2014)
The economic importance of banks to developing countries may be viewed as promoting capital formation, monetization, influencing economic activity, encouraging innovation and facilitator of monetary policy. Banking sector performance evaluation is an effective measure and indicator to check the soundness of economic activities of an economy. This study attempts to evaluate bank's performance of the GCC region using CAMEL framework. The study examines 12 conventional banks in six GCC countries where year-end financial data from the years 2008 until 2012 were gathered from the banks' annual reports and Thomson Reuters, Data stream in the library of Universiti Utara Malaysia. The study finds that capital adequacy parameters of GCC banks are above the minimum requirement, while asset quality in the GCC countries affected the bank's performance except in Saudi Arabian banks. Management quality affects banks performance in all GCC countries except in Saudi Arabian banks. Earning ability is efficient with the banks performing well during the five years under investigation. Liquidity stood in the top position for all the 12 banks in GCC countries. The GCC countries could further improve the performance of their asset quality and management quality, using CAMEL framework as it is the best model and useful in evaluating banks performance.